Learning to Live with Cheaper Oil : Policy Adjustment in MENA and CCA Oil-Exporting Countries - Sommer, Martin (Departmental Papers; Departmental Paper ;, 2016)
This paper discusses the challenges posed by low oil prices in the MENA and CCA regions, the adjustment policies adopted so far, and remaining adjustment needs and future risks.